Cystathionine γ-lyase inhibits mitochondrial oxidative stress by releasing H2S nearby through the AKT/NRF2 signaling pathway - Xiao, Tingting; Chen, Shun; Yan, Ge; Zheng, Junmin; Qiu, Qingzhu; Lin, Shujia; Zong, Yanfang; Chang, Haishuang; Yu Chang, Alex Chia; Wu, Ying; Hou, Cuilan (Frontiers in Pharmacology, 2024)
Cystathionine γ-lyase (CSE) is a major enzyme that produces hydrogen sulfide (H2S). Herein, we report how CSE plays a previously unknown role in regulating the antioxidant effects of the mitochondria in human umbilical vein endothelial cells by releasing H2S nearby under stress conditions. We found that H2S partially promoted angiogenesis in the endothelial cells through the AKT/nuclear factor erythroid 2-related factor 2 (AKT/NRF2) signaling pathway. H2S improved mitochondrial function by altering the expressions of the mitofusin2 and dynamin-1-like mitochondrial fission proteins to inhibit oxidative stress and enhance NRF2 nuclear translocation. CSE is located only in the cytoplasm and not in the mitochondria, but it is transported to the vicinity of the mitochondria to produce H2S, which plays an antioxidant role in human umbilical vein endothelial cells under stress. The CSE mutant (with mutated CSE activity center: CSED187A) partially decreased the effects on promoting angiogenesis, resisting oxidative stress, and entering the mitochondria. These results show that CSE translocation is a unique mechanism that promotes H2S production inside the mitochondria under stress stimulation. Therefore, the CSE mutant site (CSED187A) may be a potential target for drug therapy.